The Effectiveness of Macroprudential Policy in Stabilizing the Indonesian Rupiah Before and During the Covid-19 Pandemic - Suhendi, Suhendi; Fadlan, Ahmad; Karo, Ruth Silvania Br (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2024)
Macroprudential policy is an advanced monetary policy made by the government through Bank Indonesia that equally maintains the stability of the rupiah exchange rate in Indonesia. Macroprudential policy is believed to be able to maintain financial stability in Indonesia. The phenomenon seen is based on LTV (Loan To Value), LDR (Loan to Deposit Ratio), CAR (Capital Adequacy Ratio), and NPL (Non Performing Loan). Meanwhile, supporting variables outside macroprudential policies such as Inflation, Gross Domestic Product, and Trade Balance are supporting variables for rupiah exchange rate stability in Indonesia. This research on the Indonesian state is based on the phenomenon before and after covid-19, to find out whether there is an impact on the rupiah exchange rate. This type of research is quantitative and the data used in this study are secondary data obtained from Bank Indonesia and the Central Bureau of Statistics of Indonesia, the data used are time series, namely from 2002 to 2021, the method used in this study is the Vector Autogression (VAR) method and the Differential Test. The results showed that macroprudential policy had an effect on the rupiah exchange rate in Indonesia and there were differences in the Indonesian rupiah exchange rate both before covid-19 and during covid-19 in Indonesia. The suggestion concluded by the author is the need for banks to record and collect bad debts in Indonesia so that financial performance through Bank of Indonesia is optimal.